2003
DOI: 10.1016/s0896-6273(02)01170-4
|View full text |Cite
|
Sign up to set email alerts
|

Glial Glutamate Transporters Mediate a Functional Metabolic Crosstalk between Neurons and Astrocytes in the Mouse Developing Cortex

Abstract: Neuron-glia interactions are essential for synaptic function, and glial glutamate (re)uptake plays a key role at glutamatergic synapses. In knockout mice, for either glial glutamate transporters, GLAST or GLT-1, a classical metabolic response to synaptic activation (i.e., enhancement of glucose utilization) is decreased at an early functional stage in the somatosensory barrel cortex following activation of whiskers. Investigation in vitro demonstrates that glial glutamate transport represents a critical step f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
208
0
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(219 citation statements)
references
References 46 publications
8
208
0
3
Order By: Relevance
“…The uptake of neuronally released glutamate and GABA by astroglia is also functional by this time (Vitellaro-Zuccarello et al, 2003). The expression of glial glutamate transporters and glutamine synthetase increase in parallel, reaching B70% to 80% of their adult values by P10 (Voutsinos-Porche et al, 2003). Functional coupling between glutamatergic neurons and astro-glia, in terms of glial glutamate transport-coupled, 2-deoxyglucose uptake, has been demonstrated in vitro for mouse P10 somatosensory cortex (Voutsinos-Porche et al, 2003), which is similar to that seen in the adult.…”
Section: Structure Of the Metabolic Modelsupporting
confidence: 58%
See 2 more Smart Citations
“…The uptake of neuronally released glutamate and GABA by astroglia is also functional by this time (Vitellaro-Zuccarello et al, 2003). The expression of glial glutamate transporters and glutamine synthetase increase in parallel, reaching B70% to 80% of their adult values by P10 (Voutsinos-Porche et al, 2003). Functional coupling between glutamatergic neurons and astro-glia, in terms of glial glutamate transport-coupled, 2-deoxyglucose uptake, has been demonstrated in vitro for mouse P10 somatosensory cortex (Voutsinos-Porche et al, 2003), which is similar to that seen in the adult.…”
Section: Structure Of the Metabolic Modelsupporting
confidence: 58%
“…It is significant that this pattern of 'functional' glucose use in the cortex is not seen for ketone bodies (Auestad et al, 1990;Nehlig and Pereira de Vasconcelos, 1993), where utilization remains homogeneous and declines rapidly after weaning. These findings suggest that glucose (and glycolysis) supports a critical function(s) in the expression of developing neural activity (Novotny et al, 2001;Takagaki, 1974;Voutsinos-Porche et al, 2003) not provided by other fuels.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…We found that the increase in FDG uptake during QA injection was significantly higher in the lenti-CNTF group. It has been proposed that glutamate uptake by glial transporters, which accounts for 80% of total uptake in the striatum (Rothstein et al, 1996), is coupled to glucose uptake from blood stream (Pellerin and Magistretti, 1994;Voutsinos-Porche et al, 2003) by a stoichiometry close to 1:1 (Sibson et al, 1998). Therefore, the higher FDG uptake during QA injection in the lenti-CNTF group may reflect an enhanced glutamate uptake by activated astrocytes.…”
Section: Cntf Improves Glutamate Handling and Energy Supplymentioning
confidence: 99%
“…Shulman et al (2001b) suggested that 80% of energy use is correlated with glutamate passing through the glutamate-glutamine cycle and, therefore, excitatory active signaling processes ( [Sibson et al, 1998] and [Shen et al, 1999]). Astrocyte glutamate transporters have been proposed to coordinate Glc and O 2 usage in the central nervous system, linking energy production to synaptic glutamate release ( [Magistretti and Pellerin, 1999a], [Magistretti and Pellerin, 1999b] and [Voutsinos-Porche et al, 2003]). In this context, it is also important to note that glutamate taken up by astrocytes is not only converted to glutamine.…”
Section: The Energy Budget For Cellular Workmentioning
confidence: 99%